Study of $D_J$meson decays to $D^+π^-$, $D^0 π^+$ and $D^{*+}π^-$ final states in pp collisions - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (Springer Berlin Heidelberg, 2013)
A study of D +π−, D 0π+ and D ∗+π− final states is performed using pp collision data, corresponding to an integrated luminosity of 1.0 fb−1, collected at a centre-of-mass energy of 7 TeV with the LHCb detector. The D 1(2420)0 resonance is observed in the D ∗+π− final state and the D∗2(2460) resonance is observed in the D +π−, D 0π+ and D ∗+π− final states. For both resonances, their properties and spin-parity assignments are obtained. In addition, two natural parity and two unnatural parity resonances are observed in the mass region between 2500 and 2800 MeV. Further structures in the region around 3000 MeV are observed in all the D ∗+π−, D +π− and D 0π+ final states.